2022
DOI: 10.3390/jcm11102681
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Autoimmune Liver Diseases

Abstract: SARS-CoV-2 infection can trigger autoimmune responses, either by a systemic hyperstimulation of the immune system or molecular mimicry (or both). We here summarize the current knowledges about autoimmune liver diseases (AILDs) and COVID-19, focusing on (a) the risk of SARS-CoV-2 infection in patients affected by AILDs and/or under pharmacological treatment with immunosuppressants; (b) the capability of vaccination against SARS-CoV-2 to trigger autoimmune responses in the liver; and (c) the efficacy of vaccines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 43 publications
0
15
0
1
Order By: Relevance
“…Regarding patients with AIH, it has been hypothesized that their immunosuppressive state can predispose them to SARS-CoV-2 infection and a greater risk for severe disease. In particular, the SARS-CoV-2 virus may trigger autoimmune mechanisms in genetically predisposed subjects, hyperstimulating the immune system and exposing foreign peptides homologous to human peptides (molecular mimicry), thus leading to the development of autoantibodies [ 158 ]. However, there are scarce reports of AIH triggered by COVID-19 infection, and several confounding factors were always present [ 159 ].…”
Section: Covid-19 In Patients With Pre-existing Chronic Liver Diseasementioning
confidence: 99%
“…Regarding patients with AIH, it has been hypothesized that their immunosuppressive state can predispose them to SARS-CoV-2 infection and a greater risk for severe disease. In particular, the SARS-CoV-2 virus may trigger autoimmune mechanisms in genetically predisposed subjects, hyperstimulating the immune system and exposing foreign peptides homologous to human peptides (molecular mimicry), thus leading to the development of autoantibodies [ 158 ]. However, there are scarce reports of AIH triggered by COVID-19 infection, and several confounding factors were always present [ 159 ].…”
Section: Covid-19 In Patients With Pre-existing Chronic Liver Diseasementioning
confidence: 99%
“…Autoimmune liver disease (AILD) includes primary sclerosing cholangitis, primary biliary cholangitis (PBC), autoimmune hepatitis (AIH), and overlapping syndromes referring to the coexistence of two autoimmune diseases[ 81 ]. COVID-19 outcomes in patients with AILD were investigated in international registry studies and retrospective case studies[ 82 ]. Combined data from three multinational registries showed that despite the use of immunosuppressive treatment, AIH patients did not seem to have a higher risk of lethal outcomes with COVID-19 compared to patients without liver disease and those with other forms of liver disease[ 83 ].…”
Section: Covid-19 In Patients With Pre-existing Liver Diseasementioning
confidence: 99%
“…AIH was occasionally observed after COVID-19 vaccination (i.e., vaccine-induced AIH) ( Figure 1 ) [ 14 , 15 ]. A recent study indicated fast uptake of the COVID-19 mRNA vaccine BNT162b2 into human liver cell line Huh7, leading to changes in the expression and distribution of long interspersed nuclear element-1 (LINE-1), which is an endogenous reverse transcriptase, and that BNT162b2 mRNA is reverse transcribed intracellularly into DNA in as fast as 6 h upon BNT162b2 exposure.…”
mentioning
confidence: 99%
“…Thus, the COVID-19 mRNA vaccine is able to enter the human liver cell line Huh7 in vitro [ 16 ]. The use of immunosuppressants has been correlated to an increase in autoimmune liver disease severity and to lower levels of anti-SARS-CoV-2 antibodies upon vaccination [ 15 ]. All of the cases with AIH and post-COVID-19 vaccination have been successfully treated with steroids [ 15 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation